2010
DOI: 10.1124/dmd.110.032987
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Transport by Plasma Membrane Monoamine Transporter: Reinvestigation and Comparison with Organic Cations

Abstract: ABSTRACT:The plasma membrane monoamine transporter (PMAT) belongs to the equilibrative nucleoside transporter family (solute carrier 29) and was alternatively named equilibrative nucleoside transporter 4. Previous studies from our laboratory characterized PMAT as a polyspecific organic cation transporter that minimally interacts with nucleosides. Recently, PMAT-mediated uptake of adenosine (a purine nucleoside) was reported, and the transporter was proposed to function as a dual nucleoside/organic cation trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 32 publications
3
44
0
Order By: Relevance
“…In addition, an evolutionarily divergent transporter (hENT4) was later shown to mediate adenosine transport in a pH-dependent manner with optimal transport occurring at approximately pH 6.0 (9). In spite of this, hENT4 is more commonly known as the plasma membrane monoamine transporter (PMAT) due to its ability to transport organic cations including biogenic amines, cationic therapeutics, and neurotoxins (9, 10). PMAT has substantial substrate overlap and inhibitor specificity with the organic cation transporters OCT1 - 3 in the SLC22 gene family (1115).…”
mentioning
confidence: 99%
“…In addition, an evolutionarily divergent transporter (hENT4) was later shown to mediate adenosine transport in a pH-dependent manner with optimal transport occurring at approximately pH 6.0 (9). In spite of this, hENT4 is more commonly known as the plasma membrane monoamine transporter (PMAT) due to its ability to transport organic cations including biogenic amines, cationic therapeutics, and neurotoxins (9, 10). PMAT has substantial substrate overlap and inhibitor specificity with the organic cation transporters OCT1 - 3 in the SLC22 gene family (1115).…”
mentioning
confidence: 99%
“…24 Organic cation substrates such as serotonin and dopamine can be transported by ENT-4 at an efficiency much higher than that of adenosine. 25 The rate of ENT4-mediated adenosine uptake is significantly enhanced by an acidic extracellular pH, and it has been proposed that ENT-4 may have a role in ischemia. 25 However, the effect of acidic pH is not only adenosine specific but also common to organic cation substrates.…”
Section: Nucleoside Transporters In the Vascular Systemmentioning
confidence: 99%
“…25 The rate of ENT4-mediated adenosine uptake is significantly enhanced by an acidic extracellular pH, and it has been proposed that ENT-4 may have a role in ischemia. 25 However, the effect of acidic pH is not only adenosine specific but also common to organic cation substrates. 26 Another major class of nucleoside transporter is concentrative nucleoside transporters (CNTs).…”
Section: Nucleoside Transporters In the Vascular Systemmentioning
confidence: 99%
“…We recently cloned and characterized a novel polyspecific organic cation transporter, designated plasma membrane monoamine transporter (PMAT) (Engel et al, 2004), the fourth member of the equilibrative nucleoside transporter family (SLC29). Unlike other SLC29 family members (i.e., equilibrative nucleoside transporters 1-3), which exclusively transport nucleosides and nucleoside analogs, but similar to the genetically unrelated OCTs, PMAT functions as a polyspecific transporter for a wide range of small hydrophilic organic cations including monoamine neurotransmitters, drugs, and toxins (Engel et al, 2004;Zhou et al, 2007cZhou et al, , 2010. We previously showed that PMAT-mediated organic cation transport is sensitive to membrane potential changes and is also influenced by extracellular pH (Engel et al, 2004;Xia et al, 2007).…”
Section: Introductionmentioning
confidence: 99%